2007
DOI: 10.1016/j.vaccine.2007.06.058
|View full text |Cite
|
Sign up to set email alerts
|

Alphaviral vector-transduced dendritic cells are successful therapeutic vaccines against neu-overexpressing tumors in wild-type mice

Abstract: While dendritic cell (DC) vaccines can protect hosts from tumor challenge, their ability to effectively inhibit the growth of established tumors remains indeterminate. Previously, we have shown that human DCs transduced with Venezuelan equine encephalitis virus replicon particles (VRPs) were potent stimulators of antigen-specific T cells in vitro. Therefore, we investigated the ability of VRPtransduced DCs (VRP-DCs) to induce therapeutic immunity in vivo against tumors overexpressing the neu oncoprotein. Trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…Previous in vitro studies using VEE replicon particles (VRP) expressing GFP to infect adult human (38) and murine bone marrow-derived DCs (BMDCs) (37) showed an upregulation in costimulatory molecules CD40, CD80, and CD86. Additional studies using VRP-transduced human DCs showed DC maturation, secretion of proinflammatory cytokines, and significant expansion of antigen-specific T cells (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous in vitro studies using VEE replicon particles (VRP) expressing GFP to infect adult human (38) and murine bone marrow-derived DCs (BMDCs) (37) showed an upregulation in costimulatory molecules CD40, CD80, and CD86. Additional studies using VRP-transduced human DCs showed DC maturation, secretion of proinflammatory cytokines, and significant expansion of antigen-specific T cells (38).…”
Section: Discussionmentioning
confidence: 99%
“…These infected immune cells then rapidly migrate to the draining lymphoid node(s) (DLN). Alternatively, GVI3000 particles can migrate directly to DLNs, where they preferentially target DCs (36,37). In both human-and mouse-derived DCs, in vitro studies have shown an upregulation of costimulatory molecules as well as secretion of proinflammatory cytokines, such as type I IFN, IL-6, and TNF after infection (37)(38)(39).…”
mentioning
confidence: 99%
“…Female mice (8 to 14 weeks) were used for all experiments. Rat Neu-expressing NT2 cells (HER2/Neu) and the 2250 (luminal A), 2225 (basal-like), and T11 (claudin-low) tumor models have been described (36)(37)(38). T12 cells were prepared by harvesting a T12 tumor from a tumor-bearing mouse, followed by manual digestion with razor blades and chemical digestion with Liberase TM (Roche) and DNase I (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Other advantages of VRP are their tropism for, and maturation of (5), DCs, which could result in enhanced T cell activation. A number of preclinical studies have reported that VRP induce potent immunity despite the presence of neutralizing antibodies (4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%